Chemical Removal of Cordon Bunches in Dried Grape Production - Unwin, D.J.; Singh, D.P.; Hancock, E.A.; Downey, M.O. (South African Journal of Enology and Viticulture, 2016)
The Shaw swing-arm trellis has increased mechanisation in dried grape production as it enables trellis drying of the grapes in the vineyard. However, cordon bunches that do not dry reduce the quality of dried fruit at harvest. Traditionally, foliar application of ammonium nitrate was used to remove cordon bunches, but results were inconsistent. In recent years, health and safety concerns have heavily restricted the use of ammonium nitrate in the agricultural sector. Use of alternate chemical treatments was investigated to find an alternative to ammonium nitrate for removal of cordon bunches in Carina Currant, Sultana and Sunmuscat dried grape production. Different doses of calcium nitrate and Ethrel® (21.7%, w/v, ethephon) were applied to grapevines at various stages of vine growth. Calcium nitrate applied at a rate of 2.6% (w/v) to the vine pre-bloom at the 6 to 8 leaf stage (LS) and 250 ppm Ethrel® applied at full bloom (10 to 12 LS) achieved the most effective results. Both treatments provide a cost effective alternative to ammonium nitrate without any significant negative impact on growth, fruit bearing of vines and yield in the following year. Separate application scheduling of calcium nitrate (at pre-bloom) and Ethrel® (at full-bloom) offers flexibility in spray (application) schedules a management practices.